Disparities in SO₂ Exposure among Gas Station Operators in Mountainous and Urban Areas - Muhammad Syafii; Luci Riani Br. Ginting; Layari Tarigan; Fadlilah Widyaningsih (JURNAL KESMAS DAN GIZI (JKG), 2026)
High traffic density contributes significantly to air pollution through motor vehicle exhaust emissions, particularly sulfur dioxide (SO₂), which poses a risk of respiratory disorders among outdoor workers such as gas station operators. Climatic conditions and regional topography influence SO₂ concentrations in mountainous and urban areas, as well as the associated health impacts in the form of respiratory disorders. This study aimed to analyze differences in SO₂ concentrations between mountainous and urban areas and to examine the effect of SO₂ exposure on respiratory disorders among gas station operators. A quantitative comparative approach with a cross-sectional study design was employed. The study was conducted at gas stations located in both mountainous and urban areas from October 2024 to February 2025. The study population consisted of all gas station operators totaling 78 individuals, with 39 operators from each area. The sample size was 78 respondents, selected using a total sampling technique. Data were collected through interviews and observations, along with measurements of SO₂ concentrations. Data analysis was carried out in two stages: univariate analysis and bivariate analysis using independent t-tests and logistic regression, with a significance level of 95% (α=0.05). The results showed a significant difference in SO₂ concentrations between mountainous and urban areas (p-value=0.001). Furthermore, SO₂ exposure was found to have a significant effect on respiratory disorders among gas station operators (p-value=0.004; Exp(B)=1.859). SO₂ concentrations were lower in mountainous areas compared to urban areas, indicating that urban environments contribute more substantially to respiratory disorders.It is recommended that PT Pertamina provide appropriate respiratory protective equipment, such as masks, for gas station operators and implement policies mandating their use during working hours.